Latent Factors in the Management in the National Economy of Ukraine - Ptashchenko, Liana; Svistun, Lyudmila; Volkova, Valeriya; Khudolii, Yuliia (International Journal of Engineering and Technology, 2018)
To confirm the author's hypothesis about what the negative impact on the state of the national economy have not so much economic or political factors, but latent character factors. The influence of latent factors on macroeconomic processes is considered. Many factors influence the state of the national economy of Ukraine, where it is possible to consider an extended reproduction of shadow financial relations in the country. The main issue of shadowing the financial cash-flows lies in use of financial institutions, especially banks, insurance companies, stock brokers, credit groups to inefficiently withdraw funds, to evade taxes and to avoid legalization of profit, earned through crime. The terms of management put forward the objective necessity of the study of the latent factors that hinder the economic convergence of Ukraine with the standards of the leading developed countries, particularly in Europe. The research of scientific publications on problems, materials s of rating organizations and statistics data has allowed the authors to suggest synergetic idea of combining the processes of state management and social self-organization optimally, the necessity to involve scientists and society to develop implement and monitor methods of anti-corruption, as the main threat to economic security and further development of Ukraineâ€™s national economy.To achieve the purpose the complex of general scientific and special methods was used: abstract logical, monographic, induction and deduction, theoretical generalization and systematization â€“ to determine and generalize theoretical and methodological foundations of latent management as a systemic factor of shadow economy; the semantic method was to define the terms; dynamic methods and comparative analysis, Pareto, expert assessments were used to confirmation of the dominant negative influence of latent factors on the national economy.Forming the conceptual methods of mitigation of the impact of destructive latent management in the shadow sector on the national economy of Ukraine.Forming the perception about the influence of latent management as a destructive factor on the stability of existence of negative factors in the national economy of Ukraine, that is a barrier of economic convergence to the EU.Â Â